Konsep & Desain Fasilitas Olah Raga Terpadu Desa Caturharjo, Kecamatan Pandak, Kabupaten Bantul - rachmat budihardjo (Seminar Nasional Penelitian dan Abdimas, 2024)
Abstract Caturharjo Village, Pandak Distriict, Bantul Regency has a lot of potential, including natural resources, human resources and community self-help which can be developed as a Tourism Village. The Caturharjo Village area includes hills, irrigated and rain-fed rice fields. For this reason, it is very suitable as a maountainous and agricultural agra area. Apart from that, the potential for art, community activity in sports, cultural and craft activities is also very supportive, Community Service Activities (ABDIMAS) which is part of the collaboration between the Regional Planning Agency (Bappeda) of the Bantul Regency Government and the Architecture Study Program, Faculty of Engineering, Atma Jaya University Yogyakarta. The activity program that will be carried out is making a plan and design of sport facilities which is named the activity “Concept and Design of Integrated Sports Facilities, Caturharjo Villages, Pandak District, Bantul Regency”. The aim is to provide assistance to the community through the Community Partnership-Based Design Service Program. The method used to achive this goals is problem solving through a bottom-up planning and design process (based on the ideas of the user community) through Focus Group Discussions (FGD). Keywords : Concept and Design, Sports Facilities, Integrated